Liver saturated fat content associates with hepatic DNA methylation in obese individuals - Ratika Sehgal; Alexander Perfilyev; Ville Männistö; Jyrki Ågren; Emma Nilsson; Pirjo Käkelä; Charlotte Ling; Vanessa D. de Mello; Jussi Pihlajamäki (Clinical Epigenetics, 2023)
Abstract Background Accumulation of saturated fatty acids (SFAs) in the liver is known to induce hepatic steatosis and inflammation causing non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH). Although SFAs have been shown to affect the epigenome in whole blood, pancreatic islets, and adipose tissue in humans, and genome-wide DNA methylation studies have linked epigenetic changes to NAFLD and NASH, studies focusing on the association of SFAs and DNA methylation in human liver are missing. We, therefore, investigated whether human liver SFA content associates with DNA methylation and tested if SFA-linked alterations in DNA methylation associate with NAFLD-related clinical phenotypes in obese individuals. Results We identified DNA methylation (Infinium HumanMethylation450 BeadChip) of 3169 CpGs to be associated with liver total SFA content (q-value < 0.05) measured using proton NMR spectroscopy in participants of the Kuopio Obesity Surgery Study (n = 51; mean ± SD:49.3 ± 8.5 years old; BMI:43.7 ± 6.2 kg/m2). Of these 3169 sites, 797 overlapped with previously published NASH-associated CpGs (NASH-SFA), while 2372 CpGs were exclusively associated with SFA (Only-SFA). The corresponding annotated genes of these only-SFA CpGs were found to be enriched in pathways linked to satiety and hunger. Among the 54 genes mapping to these enriched pathways, DNA methylation of CpGs mapping to PRKCA and TSPO correlated with their own mRNA expression (HumanHT-12 Expression BeadChip). In addition, DNA methylation of another ten of these CpGs correlated with the mRNA expression of their neighboring genes (p value < 0.05). The proportion of CpGs demonstrating a correlation of DNA methylation with plasma glucose was higher in NASH-SFA and only-SFA groups, while the proportion of significant correlations with plasma insulin was higher in only-NASH and NASH-SFA groups as compared to all CpGs on the Illumina 450 K array (Illumina, San Diego, CA, USA). Conclusions Our results suggest that one of the mechanisms how SFA could contribute to metabolic dysregulation in NAFLD is at the level of DNA methylation. We further propose that liver SFA-related DNA methylation profile may contribute more to hyperglycemia, while insulin-related methylation profile is more linked to NAFLD or NASH. Further research is needed to elucidate the molecular mechanisms behind these observations.